Pengaruh Good Corporate Governance terhadap Nilai Perusahaan pada Perusahaan Sektor Pertambangan yang Listing di Bursa Efek Indonesia (BEI) pada Tahun 2016-2020 - Adawiyah, Romadona; Lidyah, Rika; Hartini, Titin (Intelektualita, 2022)
This study aims to determine the effect of Good Corporate Governance on Firm Value. The data used in this study is secondary data obtained by researchers through the financial statements of mining sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. Sampling in this study is by using a purposive sampling technique as many as 12 companies. This study was analyzed using review 9. The results of this study found that The board of commissioners (GCG) has a positive and significant effect on firm value and The audit committee has a positive and significant effect on firm value